Timing of Tocilizumab Administration Under the Guidance of IL-6 in CAR-T Therapy for R/R Acute Lymphoblastic Leukemia - Zhang, Yinqiang; Zhou, Fen; Wu, Zhuolin; Li, Yingnan; Li, Chenggong; Du, Mengyi; Luo, Wenjing; Kou, Haiming; Lu, Cong; Mei, Heng (Frontiers in Immunology, 2022)
Chimeric antigen receptor T (CAR-T) cells targeting CD19 have achieved great clinical responses in patients with relapsed or refractory (R/R) acute B lymphoblastic leukemia. However, severe adverse events such as cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome restrict it to further application. Tocilizumab is the corner stone for the treatment of severe CRS. It has been used to mild CRS in recent years, whereas some statistical supports are lack to clarify the suitable timing of its administration. 67 patients with B-ALL were treated with CD19-CART (registered at www.clinicaltrials.gov as #NCT02965092, NCT04008251) and enrolled in the study, of which 33 patients received Tocilizumab. Application of Tocilizumab in patients with grade 2 CRS in ASTCT criteria can significantly shorten the duration of CRS without affecting side effects and long-term efficacy. However, a section of patients still developed severe CRS with early use of Tocilizumab, indicating the significance of introduction of clinical laboratories to assist medications. Statistically, patients with less than 4-fold increase in IL-6 levels had a higher incidence of severe CRS after receiving Tocilizumab (37.5% versus. 0%, P=0.0125), which provided a basis for refining CRS intervention strategies under the guidance of IL-6.